STUDI ANALISIS GERAK TEKNIK BLOCK BOLA VOLI PADA ATLET KLUB SURVOTE SUNGAI RAMBAI - Wisnu; Ugi Nugraha; Iwan Budi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the movement technique of volleyball blocking among athletes of the Survote Volleyball Club in Sungai Rambai. The background of this research was based on the low success rate of blocking during matches, where opponents could easily penetrate the team’s defense. Blocking is considered an essential defensive technique in volleyball because it plays an important role in preventing opponent attacks and gaining points. Therefore, proper movement coordination from the preparation phase to landing is required to perform an effective block.This research used a descriptive quantitative method. The population and sample consisted of 12 female athletes from the Survote Volleyball Club. Data were collected through observation sheets assessed directly by the club coach. The assessment focused on four movement phases of blocking technique, namely the preparation phase, take-off phase, airborne position, and landing phase. The collected data were analyzed using percentage calculations, averages, and standard deviations.The results showed that the athletes’ blocking technique ability was generally categorized as moderate, with an average final score of 58.25. The highest score obtained was 66, while the lowest score was 50, with a standard deviation of 4.51. The best performance aspect was the take-off phase, whereas the weakest aspect was the airborne position. Most athletes still experienced difficulties in hand positioning, wrist activity, and body stability while in the air. In conclusion, the blocking technique of Survote athletes has not yet reached an optimal level and still requires improvement, especially in airborne and landing movements, through more structured and effective training programs.